A Review of Biosurfactants (Glycolipids): The Characteristics, Composition and Application - Kammas Abdul Kareem, Mohammed; H. Mussa, Amel (International Journal of Psychosocial Rehabilitation, 2020)
Biosurfactants are natural products with surface-active properties; they can be produced by various types of microorganisms. The biosurfactants as biological compounds had various aspects of applications in different fields of life, including environmental applications, oil recovery and bioremediation, and pharmaceutical and agricultural industries. Biosurfactants could be classified interdependently according to the molecular weight (M.W.), physicochemical exclusivity, and mode of their action. Glycolipids, one of the most important biosurfactants, include rhamnolipids, trehalolipids, and sophorolipids, which have gained widespread attention due to their low toxicity, environmental friendliness, and ready biodegradability.